Diggers at the well : proceedings of a third International Symposium on the Hebrew of the Dead Sea Scrolls and Ben Sira - Muraoka, T.; Elwolde, J. F. (Studies on the Texts of the Desert of Judah, 2000)
The accelerated publication of the Dead Sea Scrolls makes it essential for scholars working with these texts to have reliable and up-to-date information over the nature of Qumran Hebrew and Aramaic. This volume presents results of current investigations in this field presented at a third, four-day symposium on the Hebrew of the Scrolls and Ben Sira held in October 1999 at the Ben-Gurion University in Beer-Sheva with as many as 27 papers presented, some of which deal with questions of general and fundamental importance such as the nature of Qumran Hebrew, the linguistic symbiosis in Qumran, the position of Qumran Hebrew in the history of Hebrew, the future directions of philological and linguistic investigation of Qumran Hebrew and the Scrolls. Participants, many of whom are reputed specialists in the field, came from not only Israel, but also the U.S.A. , U.K., Sweden, the Netherlands, and France.